Analysis of Factors Influencing Earnings Management Practices in Banking Companies: An Empirical Study in Indonesia Period 2019-2023 - Rusdiah Hasanuddin (Brilliant International Journal Of Management And Tourism, 2023)
Earnings management practices in the banking sector have gained significant attention following various financial scandals and regulatory changes. The banking industry's unique characteristics, including regulatory requirements and stakeholder expectations, create specific incentives for earnings management behaviors. This study aims to analyze the factors that influence earnings management practices in Indonesian banking companies during the period 2019-2023, focusing on firm-specific characteristics, corporate governance mechanisms, and regulatory factors. This quantitative study employed panel data analysis using a sample of 45 commercial banks listed on the Indonesia Stock Exchange over a five-year period (2019-2023), resulting in 225 firm-year observations. Earnings management was measured using the Modified Jones Model, while independent variables included bank size, profitability, capital adequacy, board independence, audit quality, and regulatory pressure. Panel data regression with fixed effects was employed for hypothesis testing. The findings reveal that bank size has a significant negative effect on earnings management (β = -0.234, p < 0.05), while profitability shows a significant positive effect (β = 0.312, p < 0.01). Capital adequacy ratio negatively influences earnings management (β = -0.187, p < 0.05). Board independence demonstrates a significant negative effect (β = -0.298, p < 0.01), and audit quality by Big 4 auditors reduces earnings management practices (β = -0.156, p < 0.05). The model explains 64.2% of the variance in earnings management practices (R² = 0.642). Bank-specific characteristics and corporate governance mechanisms significantly influence earnings management practices in Indonesian banking companies. Larger banks with stronger governance structures and higher capital adequacy tend to engage less in earnings management activities.